PEMBERDAYAAN MASYARAKAT MELALUI PENGKEMASAN AGROWISATA SALAK DI DESA SIBETAN KECAMATAN BEBANDEM KABUPATEN KARANGASEM - I. G. N. Widyatmaja; A. A. P. Sri; I. W. Wiraatmaja (Buletin Udayana Mengabdi, 2016)
KKN-PPM which carried out in Desa Sibetan, Bebandem, Karangasem aims to provide a wide space for localpeople to organizes and improves the system of management of salak agro tourism and to increases theparticipation of local communities in tourism development in Desa Sibetan through the well – packaging ofsalak agro tourism. In order to increase the income of local communities in Sibetan village, it is important toheld this community empowerment through the utilization of its potencies, and then package it, as a valuabletourism product as well as to improve the finance and the power sources of those communities, also as a supportof the tourism development in Karangasem. The targets of the activities of KKN – PPM are the agro tourismmanager and the young generations of Sibetan village. The approaching models are: 1. Participatory RuralAppraisal (PRA) Model, (2) Entrepreneurship Capacity Building (ECB) Model, (3) Knowledge/TechnologyTransfer Model. Some activities have been done in KKN – PPM program in Desa Sibetan, in order to addressthe various problems of salak agro – tourism faced by the local communities of Sibetan village, such as: Setting– up a sort of a foundation to manage the agro – tourism in Desa Sibetan, tour guide traning for the localcomunities, packaging training in how to package the salak processed products into tourism products, Englishfor tourism courses, and provide the local communities houses as home stays for the tourists.